Percutaneous Penetration Enhancers Chemical Methods in Penetration Enhancement Drug Manipulation Strategies and Vehicle Effects - Dragicevic, Nina; Maibach, Howard I. (Springer Berlin Heidelberg : Imprint: Springer, 2015)
This truly comprehensive reference, in a mini-series format with five volumes, offers a detailed description of both well-known and recently introduced methods for percutaneous penetration enhancement. The first three volumes are devoted to the broad range of chemical methods used to enhance the skin delivery of drugs, including the vast variety of chemical penetration enhancers, drug and vehicle manipulation strategies, nanocarriers, and many others. The fourth volume discusses the diverse physical methods used in penetration enhancement, such as sonophoresis, iontophoresis, electroporation, microporation, laser ablation, and microneedles. Determination of drug penetration is covered in the final volume, with a focus especially on mathematics in skin permeation and modern analytical techniques adapted to assess and measure penetration. This edition of Percutaneous Penetration Enhancers will be an invaluable resource for researchers, pharmaceutical scientists, practitioners, and also students.